Conservative Style, Liberal Production: Hemudu’s Binary System for Maintaining its Scapular Shovel Tradition in the Southern Yangzi Delta, 7000–6000 BP - Xie, Liye; Lun, Casey; Jiang, Leping; Sun, Guoping (Frontiers in Earth Science, 2021)
We examined the scapular implements of early Hemudu cultures (7000-6000 BP) in southern Yangzi Delta to understand the linkage between learning and maintaining the scapular shovel tradition in the Hemudu culture's socio-economic context. We first traced scapular tool’s history in the region to the precedent Kuahuqiao culture (8200-7000 BP), then used published results of replication experiment to identify the product traits pertinent to craft learning and identify the learning and production patterns of the Hemudu scapular shovel blades. Hemudu scapular shovels had a consistently unique, complicated hafting style and a raw material preference for old water buffalo scapulae. However, our research shows that the shovel blades’ morphological details and technical solutions varied significantly. In addition, most finished products display manufacturing mistakes that reveal a lack of skills, experience, and intervention, suggesting the production of naïve crafters. In addition, practice pieces are rare compared to the number of finished and used products. Although additional evidence implies that practice might have been more common than the studied sample suggested, it was carried out with less-than-ideal bones and thus insufficient for developing technical competency. We argue that the Hemudu societal norms for a scapular shovel applied only to the highly visible aspects of the implement. The shaft and ligatures could reduce the visibility of many manufacturing flaws on the shovel blade to reach the desired visual effect of the shovel. The shovel blades were made by household crafters familiar with them but had insufficient training and practice in manufacturing emulating from an artifact or a memorized template. Communities of practice were minimal to nonexistent among the shovel makers; alternative mechanisms to maintain the technical norms or hold a high product standard were also lacking. Therefore, we concluded that the scapular shovels were less important as a technical implementation than a visual communicator of social identity. The Humudu’s binary system of conformist style and material preference mixed with loose quality control in the shovel blade production reveals that social conformity and the associated learning pattern are circumstantial and fluid even for a community's iconic implement.